Antimicrobial Efficacy of Endomethasone and Sealapex Sealers against Specific Endodontic Pathogens (City Dental College Journal, 2013)
Background: Antimicrobial efficacy is one of the desired properties of root canal sealer to eliminate the residual microorganisms from complex root canal system unaffected by chemomechanical preparation and intracanal medication. The aim of the study is to compare the antimicrobial effects of two different sealers, i.e. zinc oxide based Endomethasone and calcium hydroxide based Sealapex against E. faecalis, S. aureus and C. albicans which are considered most resistant microorganisms in the oral cavity. Methods: Agar diffusion method was used in this study. The sealers were prepared according to manufacturers instruction and placed in prepared wells 36 agar plates inoculated with E. faecalis, S. aureus and C. albicans. All plates were incubated for 5 days at 370C. The zone of inhibition of each sealer was measured after 24 hours, 48 hours and 5 days interval in order to evaluate the antimicrobial efficacy in different time duration. Statistical analysis was performed by ANOVA, independent sample t test and paired t test as applicable. P value